Risk management in road construction: The case of Sri Lanka - Perera, B.A.K.S; Dhanasinghe, Indika; Rameezdeen, Raufdeen (International Journal of Strategic Property Management, 2009)
Risk is an unavoidable phenomenon in construction projects. Proper risk allocation in construction contracts has therefore come to assume prominence because risk identification and risk allocation have a clear bearing on risk handling decisions. The proper management of risks requires that they be identified and allocated in a well‐defined manner. This can only be achieved if contracting parties comprehend their risk responsibilities, risk event conditions, and risk handling capabilities. This research aims at identifying the risk responsibilities of contractual parties in order to improve their risk handling strategies with regard to Sri Lankan road projects. Semi‐structured interviews were used for the primary data collection. This was complemented with documentary evidence. The results show that road construction projects in Sri Lanka are exposed to many risk sources while most risks are borne by parties who were assigned with risks via contract clauses. However, parties not allocated with risks too happened to bear the consequences of such risks. Therefore, it is concluded that there is no one best way to respond to a risk and that different risk handling strategies should be adopted in order to deal effectively with risks. First Publish Online: 18 Oct 2010